Approximations on the concept of property in Locke and Schopenhauer - Edart, Vinícius (2024)
Second The aim of this article is to analyze the concept of property in the theory of Arthur Schopenhauer's theory, contained mainly in the work Parerga und Paralipomena and John Locke's theory, expressed in the Second John Locke's theory, expressed in the Second Treatise on Civil Government, and to establish relationships between the concepts, in order to demonstrate their similarities as a natural right and their differences as a differences as positive law in the theory of the two philosophers.